Method for quality assessment of image mosaic - Guo-ting WAN; Jun-ping WANG; Jin LI; Hong-hua CAO; Song WANG; Le WANG; IYA-ning L; Rong WEI (Tongxin xuebao)
On the basis of the theory of existing methods for image quality assessment,a novel method for quality assessment of mosaicked image based on the information of image edge was presented.The method was in accordance with the features of mosaicked image.Firstly,the edges of image were detected.Then according to the information of image edges,the information of pixel error and structure was considered.The mean value and variance of the difference of edge map were related with the misplacement and the brightness mutation,which influenced the quality of mosaicked image.Lastly,the evaluate procedure was done based on the relationship.The new method was more consistent with the subjective feeling to the mosaicked image quality.This method accurately reflects the real quality of mosaicked image and the performance of the algorithm of image mosaic.